Performance Analysis of Direct Stage, In-Direct Stage and Two-Stage Evaporative Air Cooler - San, Thiri; Aung Ko Latt; War War Min Swe; Yin Yin Aye (The Indonesian Journal of Computer Science, 2026)
Evaporative coolers are used in various areas especially in dry, hot climates in weather. This research focus on the theoretical and experimental result of the evaporative air cooler. There are three types of evaporative air coolers. They are direct evaporative air cooler, indirect evaporative air cooler and two-stage evaporative air cooler. Evaporative air cooler can provide summer comfort conditions as an environmentally clean, fresh supply air and energy efficient cooling system for some regions of our country where direct system alone is not suitable. In this paper, the tube type heat exchanger was used ad the tubes are made with copper and water is passed through the copper tube with 20˚C. This model then has been adapted for two-stage, indirect and direct stages. Therefore, the cooling capacity of two-stage is 2.95 kW and direct stage and in-direct stage is 2.65 kW respectively. Therefore, the cooling efficiency of two-stage is 90% the direct stage is 84% and the in-direct stage is 80% of evaporative air cooler. So, two-stage evaporative air cooler was performed more than direct and in-direct stage evaporative air cooler.